Antegrade Intramedullary Fixation for Clavicular Shaft Fracture: A Technical Trick. Issue 3 (March 2022) - Youn, Seung-Min; Kim, Jong Dae; Jeong, Ho Yeon; Ro, Kyunghan; Kim, Myung Seo; Rhee, Yong Girl; Rhee, Sung-Min
Abstract : Summary: The standard open reduction and internal fixation technique with a plate and screws for a simple mid shaft clavicular fracture necessitates a relatively large incision and can also lead to variable amount of keloid scar formation. Historically, other techniques of more minimally invasive retrograde intramedullary fixation with the entry point posterolaterally on the shoulder have shown their own disadvantages and complications. We present a surgical technique of antegrade intramedullary fixation for mid shaft clavicular fractures and an illustrative case series. Abstract : Supplemental Digital Content is Available in the Text.